Personalized Nutrition in Food Allergy: Tips for Clinical Practice - D'Auria, Enza; Pendezza, Erica; Zuccotti, Gian Vincenzo (Frontiers in Pediatrics, 2020)
Nowadays, food allergies are considered as a wide spectrum of disorders that need different approaches. The “one size fits all” approach is giving way to a “targeted approach,” based on the identification of the patient's phenotype. Thus, the approach of nutritional management of food allergy has moved on from simply being “yes or no” to “how much?”, “in which form?” and “for which patients?” Different factors should be considered in order to make a patient-tailored nutritional plan in clinical practice. Tailored nutritional plans may help to reduce the nutritional, social and economic burden of food allergy.